NASKAH PUBLIKASI PERANCANGAN APLIKASI PENCARIAN BENGKEL NASMOCO MENGGUNAKAN LOCATION BASED SERVICE (LBS) DIKARESIDENAN SEMARANG BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstract Car repair shops have an important role to users. In the event of damage to the car is suddenly on the move or want to serve in areas that have not known necessarily motorists need the services of a nearby garage at the time driver position. However, the presence information as Nasmoco quality workshop in Semarang and surrounding area yet. So that motorists submit any repairs to the garage which is not uncommon workmanship and parts kulitasnya less assured. Mobile applications built Nasmoco search workshop can help with the above. Subjects of this study is to design a mobile application search Nasmoco workshop in Semarang karesidenan based Location Based Serviced (LBS). In the development of this application using Eclipse and the Google API. While searching the user's position utilizing Global Positioning System (GPS) and Driving Route. The system is able to display the path and the time required for the workshop Nasmoco location to be addressed by the user. Of applications that have been created the application can provide the longest and shortest path and show the path to the destination and can provide information about the distance between the user's position with Nasmoco workshop location in Google Direction karesidenan semarang based API. Keyword :  Nasmoco, Mobile, Android, GPS (Global Positioning System), Google Maps API, LBS (Location Based Service).